1990
DOI: 10.1177/104063879000200118
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility of Pasteurella Multocida Type D from Missouri Swine

Abstract: Atrophic rhinitis (AR) is a significant disease and management problem to swine producers worldwide. 1,9 For some time, Bordetella bronchiseptica was considered to be the primary etiologic agent of AR. 7,10 However, current evidence indicates that toxigenic strains of Pasteurella multocida type D may also play a role in this disease process. 1,9 Pasteurella multocida type D is a fastidious microorganism, and often, when taken from turbinates, it will not initially grow on standard blood agar (trypticase soy wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
4
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 3 publications
6
4
0
Order By: Relevance
“…Ampicillin demonstrated excellent activity against P. multocida, ␤-hemolytic streptococci, and S. suis (MIC 90 s, Յ0.03, Յ0.03, and 0.13 g/ml, respec-tively) and moderate activity against S. typhimurium (MIC 90 s, 2.0 g/ml). These results are in agreement with previously reported MICs (10,33,34). Fales et al (10) found the MIC 90 of ampicillin to be Յ0.25 g/ml for P. multocida.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Ampicillin demonstrated excellent activity against P. multocida, ␤-hemolytic streptococci, and S. suis (MIC 90 s, Յ0.03, Յ0.03, and 0.13 g/ml, respec-tively) and moderate activity against S. typhimurium (MIC 90 s, 2.0 g/ml). These results are in agreement with previously reported MICs (10,33,34). Fales et al (10) found the MIC 90 of ampicillin to be Յ0.25 g/ml for P. multocida.…”
Section: Resultssupporting
confidence: 92%
“…These results are in agreement with previously reported MICs (10,33,34). Fales et al (10) found the MIC 90 of ampicillin to be Յ0.25 g/ml for P. multocida. Turgeon et al (34,35) found that Ն90% of strains of S. suis were inhibited by 0.12 g of ampicillin per ml.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…24 Lung of each specimen was cultured for P. multocida, A. pleuropneumoniae, and S. cholerae-suis as previously described. 3,[5][6][7]23 Lung was cultured for Mycoplasma spp. as previously described in specimens with typical gross lesions.…”
mentioning
confidence: 99%
“…This may be especially true of those swine that had received antibiotics, because there are differences in the antimicrobial susceptibility patterns of these bacteria. [5][6][7] The isolation and identification of A. pleuropneumoniae requires special bacteriologic media and techniques. 3,22 Actinobacillus pleuropneumoniae has been isolated by dilution techniques from Table 2.…”
mentioning
confidence: 99%